The relationship between age, education and work experience with job performance and social pain among nurses - Al-Neami, Ibrahim Ahmed; Tamrin, Shamsul Bahri; Khuan, Lee; Guan, Ng Yee (Nova Science, 2022)
Job performance in nursing is depending on many aspects, such as the level of education, age, individual characteristics, stress and anxiety level. In this review paper we have tried to collect the relevant data from 2015 until 2021 using selected keywords including age, education and social pain. Scopus, PubMed, and Web of Science were the main sources for this search. The findings of this paper confirmed the importance of education and age in relation to job performance and social pain.